2013
DOI: 10.1002/tee.21884
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials affected by spatial frequencies of background visual pattern during a cognitive task

Abstract: Spatial variation in luminance, which is one of the most important attributes of a visual image, may cause characteristic reactions in higher order brain functions. We aim to characterize the event‐related potentials (ERPs) associated with a cognitive task (simple addition) in terms of how they are influenced by the spatial frequencies of the background visual pattern. We use vertically striped visual stimuli with embedded numbers (0–9) and different spatial frequency characteristics (white noise, 1/f, 1/f2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our previous study concluded that spatial frequency characteristics influenced the ERPs associated with the neural activity accompanying simple addition 4. In this study, additional analyses investigated inter‐trial variances using wavelet coefficients to discuss novel findings for ERD/ERS.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Our previous study concluded that spatial frequency characteristics influenced the ERPs associated with the neural activity accompanying simple addition 4. In this study, additional analyses investigated inter‐trial variances using wavelet coefficients to discuss novel findings for ERD/ERS.…”
Section: Discussionmentioning
confidence: 91%
“…Because the EEG data obtained from our previous experiment is used in this study, the visual stimulus, task, subjects, and EEG recordings are all as described in detail in our previous paper 4. Briefly, four types of vertically striped visual stimuli were presented to subjects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations